Serum chemokine IL-8 acts as a biomarker for identifying COVID-19-associated persistent severe acute kidney injury - Zhi He; Jing-jing Liu; Shao-lei Ma (Renal Failure)
Objectives Persistent severe acute kidney injury (PS-AKI) is associated with poor clinical outcomes. Our study attempted to evaluate the diagnostic value of chemokines for early-stage PS-AKI prediction.Methods According to the KDIGO criteria, 115 COVID-19 patients diagnosed with stage 2/3 AKI were recruited from the intensive care unit between December 2022 and February 2023. Primary clinical outcomes included detecting PS-AKI in the first week (≥ KDIGO stage 2 ≥ 72 h). Cytometric Bead Array was used to detect patient plasma levels (interleukin-8 (IL-8), C-C chemokine ligand 5 (CCL5), chemokine (C-X-C Motif) ligand 9 (CXCL9), and interferon-inducible protein 10 (IP-10)) of chemokines within 24 h of enrollment.Results Of the 115 COVID-19 patients with stage 2/3 AKI, 27 were diagnosed with PS-AKI. Among the four measured chemokines, only the IL-8 level was significantly elevated in the PS-AKI group than in the Non-PS-AKI group. IL-8 was more effective as a biomarker while predicting PS-AKI with an area under the curve of 0.769 (0.675-0.863). This was superior to other biomarkers related to AKI, including serum creatinine. Moreover, plasma IL-8 levels of >32.2 pg/ml on admission could predict PS-AKI risk (sensitivity = 92.6%, specificity = 51.1%). Additionally, the IL-8 level was associated with total protein and IL-6 levels.Conclusion Plasma IL-8 is a promising marker for the early identification of PS-AKI among COVID-19 patients. These findings should be validated in further studies with a larger sample size.